2014
DOI: 10.1111/pme.12244
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Knowledge of Pain Management in Patients Receiving Outpatient Cancer Treatment: What Do Older Adults Really Know about Their Cancer Pain?

Abstract: Objective An individual’s ability to effectively manage their cancer pain is influenced by knowledge and perceptions regarding the pain experience. While significance of the physician’s knowledge of cancer pain management has been reported, much less is known how a patient’s knowledge may influence their ability to optimally manage their pain. The purpose of this study is to determine the influence identified health and social factors have on the knowledge and experience of cancer pain among older adults. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…The independent association of education with barriers to pain management may reflect the influence of factors such as health literacy and awareness of pain management resources. For example, cancer patients with low educational attainment have been shown to be less knowledgeable of resources for managing cancer pain compared with more educated patients . Educational interventions to increase knowledge about pain and awareness of pain management options and resources may help reduce disparities to pain management among cancer survivors with less formal education …”
Section: Discussionmentioning
confidence: 99%
“…The independent association of education with barriers to pain management may reflect the influence of factors such as health literacy and awareness of pain management resources. For example, cancer patients with low educational attainment have been shown to be less knowledgeable of resources for managing cancer pain compared with more educated patients . Educational interventions to increase knowledge about pain and awareness of pain management options and resources may help reduce disparities to pain management among cancer survivors with less formal education …”
Section: Discussionmentioning
confidence: 99%
“…The enrolled population who had graduate level education and above demonstrated better knowledge regarding pain management options than those who had received lower levels of education or were illiterate. Baker et al found in their research that individuals with higher education actively seeked information regarding their treatment and discussed that information with their physicians, while lower education was found by them to be one of the barriers to receiving and understanding information regarding pain management [8]. Results of our survey demonstrated that patients who had previous surgical exposure had significantly better knowledge regarding postoperative pain management (p = 0.002).…”
Section: Discussionmentioning
confidence: 61%
“…However, ineffective postoperative pain relief still remains a common problem in health care, and it is estimated that approximately 50%-75% of patients have insufficient pain relief postoperatively [1][2][3]. One of the barriers to attaining optimal pain relief has been found to be patients' lack of knowledge regarding the options available for pain management and their potential side effects [4][5][6][7][8]. The reason for this is that a patient who is not aware of the available options would not be able to demand for them when in pain.…”
Section: Introductionmentioning
confidence: 99%
“…The experience subscale has seven items that measure pain relief, distress, and pain control. 30,42 Cronbach's alpha for this subscale was reported as 0.84. 43 The SDS questionnaire has 13 items that measure 11 symptoms associated with cancer.…”
Section: Methodsmentioning
confidence: 99%